Efficacy of parenteral rabeprazole at acute ulcer gastroduodenal bleeding in patients with high risk of relapse after endoscopic hemostasis - S. G. Shapovalyants; S. A. Chernyakevich; A. I. Mikhalev; I. V. Babkova; G. N. Storozhuk; Ye. K. Mayat; P. L. Chernyakevich (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine efficacy of ulcer bleeding treatment at high risk of relapse after endoscopic hemostasis: the baseline intensive therapy including antisecretory treatment including parenteral form of rabeloc (rabeprazole) was applied.Material and methods. Original study included overall 25 patients with acute ulcer gastroduodenal bleeding. Past history was complicated for peptic ulcer in 14 patients. Ongoing ulcer bleeding (Forrest Ia, b) was found in 5 patients. Hemostasis has been effectively carried out by combined approach (injection of epinephrine solution and argon plasma coagulation). In the other 20 patients with stopped bleeding by the time of examination preventive endoscopic hemostasis was implemented.Results. Patients received rabeloc (rabeprazole 20 mg) bolus intravenous injections every 6 hs for 3 days until high risk of bleeding relapse disappeared, followed by single-dose 20 mg intravenously for 10 days. Dynamic endoscopy on the 2, 4, 7, 14 day have been carried out in 25 patients, of them 4 patients required additional endoscopic hemostasis and continued of parenteral injection of rabeloc 20 mg every 6 hs for three days more. In all studied patients it was possible to avoid bleeding relapse. By the 4-th day of treatment in 21 (84%) patient signs of high risk of a bleeding were absent. For relatively short 2-week treatment term stomach ulcer size reduced by 54%, duodenal ulcers — by 47%, and in 24% complete healing was achieved.Conclusions. Parenteral form of second generation proton pump inhibitor rabeloc (rabeprazole) meets requirements for treatment active gastric or duodenal ulcers complicated by acute bleeding.